ChemInform Abstract: Identifying a Highly Active Copper Catalyst for KA2 Reaction of Aromatic Ketones. Issue 28 (June 2016) - Cai, Yujuan; Tang, Xinjun; Ma, Shengming
Abstract: A highly efficient catalytic protocol is developed for the coupling of aromatic ketones with amines and terminal alkynes.